MODERN TRENDS AND DEVELOPMENT PROSPECTS OF INNOVATIVE ACTIVITIES IN JOINT-STOCK COMPANIES - Ismailov Allayor Rashidovich (Scholar Express Journals, 2025)
This article analyzes current trends and development prospects of innovative activities in joint-stock companies. The main directions of introducing innovations in the global and national economy based on digital technologies, the concept of "Industry 4.0", digital corporate governance and ESG requirements are highlighted. At the same time, the issues of increasing innovative potential, ensuring competitiveness and supporting sustainable development through attracting investments and introducing advanced technologies are considered.
Keywords: technologies; requirements; trends